More blastocysts are produced from fewer oocytes in ICSI compared to IVF – results from a sibling oocytes study and definition of a new key performance indicator - Chamayou, Sandrine (Reprod Biol Endocrinol, 2021)
BACKGROUND: Which fertilization method, between ICSI and IVF in split insemination treatments, has the highest clinical efficiency in producing clinically usable blastocyst? METHODS: 211 infertile couples underwent split insemination treatments for a non-severe male factor. 1300 metaphase II (MII) oocytes were inseminated by conventional IVF and 1302 MII oocytes were micro-injected with the same partner’s semen. Embryo development until blastocyst stage on day V and clinical outcomes were valuated trough conventional key performance indicators (KPI), and new KPIs such as blastocyst rate per used MII oocytes and the number of MII oocytes to produce one clinically usable blastocyst from ICSI and IVF procedures. RESULTS: The results were  globally analyzed and according to ovarian stimulation protocol, infertility indication, and female age. The conventional KPI were online with the expected values from consensus references. From global results, 2.3 MII oocyte was needed to produce one clinically usable blastocyst after ICSI compared to 2.9 MII oocytes in IVF. On the same way, more blastocysts for clinical use were produced from fewer MII oocytes in ICSI compared to IVF in all sub-groups. CONCLUSIONS: In split insemination treatments, the yield of clinically usable blastocysts was always superior in ICSI compared to IVF. The new KPI "number of needed oocytes to produce one clinically usable embryo" tests the clinical efficiency of the IVF laboratory.